(untitled) (Physical Education, Health and Social Sciences, 2025)
The research analyzes the drug trafficking control strategies deployed by the United Nations Office on Drugs and Crime throughout Pakistan. Pakistan faces critical threats to national security combined with public health and economic issues stemming from its position in the worldwide drug trafficking hubs. Pakistani authorities together with the UNODC and international organizations work to combat this issue by launching multiple programs. This research analyzes drug trafficking strategies by investigating their operational practices and both the encountered difficulties and achieved results. This research utilizes quantitative investigation approaches to evaluate UNODC’s anti-drug trafficking efforts in Pakistan by interviewing stakeholders and examining UNODC reports with statistical drug seizure and arrest data to conduct a thorough assessment. The research identifies both potential strengths and vulnerabilities which exist in modern interventions and proposes methods to boost future intervention performance. The progress made requires more strategic collaborative work because the region needs better methods to fight its complex drug trafficking challenge. The paper examines drug trafficking in Pakistan while discussing UNODC activities together with anti-drug strategies, the narcotics trade, international cooperation, security challenges, public health aspects, drug control policies, regional security and law enforcement approaches.